A high sensitivity assay is more accurate than a classical assay for the measurement of plasma CRP levels in endometriosis - Vodolazkaia Alexandra; Bossuyt Xavier; Fassbender Amelie; Kyama Cleophas M; Meuleman Christel; Peeraer Karen; Tomassetti Carla; D'Hooghe Thomas M (BMC, 2011)
Abstract Background Endometriosis is associated with chronic subclinical inflammation. C-reactive protein (CRP), a marker of inflammation, could serve as a biomarker of endometriosis. We tested the hypothesis that a high sensitivity CRP assay (hsCRP) is more accurate than a classical CRP assay in the detection of subclinical inflammation in plasma of women with endometriosis. Methods CRP levels were measured by hsCRP and classical CRP assays in plasma of 204 women with endometriosis and 91 women without endometriosis. Both assays were compared with respect to their value for the diagnosis of endometriosis. Results The number of plasma samples with detectable CRP was significantly higher (100%) using the hsCRP assay when compared to the classical CRP assay (42.7%) (p < 0.0001). Significantly increased CRP plasma levels were found in women with endometriosis when compared with controls when the hsCRP assay was used in samples obtained during the luteal phase (p = 0.008). The highest discriminative ability for the diagnosis of endometriosis was also obtained using the hsCRP assay during the luteal phase, especially for moderate -severe endometriosis. At a cut-off level of hsCRP > 0.71 mg/L, moderate-severe stages were diagnosed with 80.7% sensitivity and 63.9% specificity during the luteal phase. Using a similar cut-off value for CRP analyzed by the classical method, moderate-severe endometriosis was diagnosed with lower sensitivity (67.7%, p = 0.06) and comparable specificity (63.9%). Conclusions The hsCRP assay was superior to the classical CRP assay for the detection of low CRP levels and for revealing subclinical inflammation in plasma of women with endometriosis.